Opinions of Students and Teachers in Primary School towards Online Learning during COVID-19 Outbreak - Prasart Nuangchalerm; Chananya Wongjamnong; Chinathip Muangou (Pedagogi: Jurnal Ilmu Pendidikan, 2021)
The purpose of this research was to study the opinions of students and teachers in primary school towards online learning during COVID-19 outbreak. The informants were 106 students and 45 teachers from one primary school, Mahasarakham province, Thailand in Semester 2 Academic Year 2020. Questionnaires were used for data collection through Google form. Percentage, mean, and standard deviation were employed for data analysis. Findings showed that students had opinions towards online learning during COVID-19 outbreak were at high level, but teachers are quite fluctuating level of their opinion between high and low levels. The discussion represents students are ready to have online learning than teachers who are not familiar with technology. Teachers need to reskill or upskill in field of educational technology within and post outbreak.